2016
DOI: 10.1111/1365-2656.12524
|View full text |Cite
|
Sign up to set email alerts
|

Fight‐flight or freeze‐hide? Personality and metabolic phenotype mediate physiological defence responses in flatfish

Abstract: Survival depends on appropriate behavioural and physiological responses to danger. In addition to active 'fight-flight' defence responses, a passive 'freeze-hide' response is adaptive in some contexts. However, the physiological mechanisms determining which individuals choose a given defence response remain poorly understood. We examined the relationships among personality, metabolic performance and physiological stress responses across an environmental gradient in the olive flounder, Paralichthys olivaceus. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 71 publications
(159 reference statements)
4
82
0
Order By: Relevance
“…Sinistral P. stellatus had greater RMR than dextrals, and although the difference was subtle, it did not differ significantly among three sampled localities ( Figure 5). Increased RMR is associated with improved swimming performance, faster recovery after exertion, behavioral boldness, and more active predator escape responses in other fishes (Killen, Mitchell et al, 2014;Marras et al, 2010;Metcalfe et al, 2016;Rupia et al, 2016;Yan, He, Cao, & Fu, 2013). Therefore, subtle RMR increases in sinistral P. stellatus could influence their swimming performance and trophic interactions and might be one factor leading to trophic segregation between morphs (Bergstrom & Reimchen, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinistral P. stellatus had greater RMR than dextrals, and although the difference was subtle, it did not differ significantly among three sampled localities ( Figure 5). Increased RMR is associated with improved swimming performance, faster recovery after exertion, behavioral boldness, and more active predator escape responses in other fishes (Killen, Mitchell et al, 2014;Marras et al, 2010;Metcalfe et al, 2016;Rupia et al, 2016;Yan, He, Cao, & Fu, 2013). Therefore, subtle RMR increases in sinistral P. stellatus could influence their swimming performance and trophic interactions and might be one factor leading to trophic segregation between morphs (Bergstrom & Reimchen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Impacts on fish swimming performance also exist, and although studies testing this effect among individuals within species are rare, findings suggest swimming performance (Metcalfe, Van Leeuwen, & Killen, ) and recovery after exercise (Killen, Mitchell et al, ; Marras, Claireaux, McKenzie, & Nelson, ) are positively associated with greater metabolic rates. Olive flounder ( Paralichthys olivaceus ) exhibit variation in personality, with bold flounder have greater metabolic rates and a more active swimming escape response to threats than shy flounder (Rupia, Binning, Roche, & Lu, ). However, to our knowledge the association between metabolic rate and swimming performance has not been demonstrated for P. stellatus , nor have metabolic differences between morphs been assessed in other polymorphic flatfishes.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of "intermediate" individuals is common when working with domestic species due to low environmental challenge (Boersma 2011). Despite the extensive range of behavioural methodologies used, different suites of personality traits have been observed in many animal species (Réale et al 2007, Briffa et al 2013, Montiglio et al, 2014 and multiple fish species including the olive flounder, Paralichthys olivaceus (Rupia et al, 2016), Mulloway Argyrossomus japonicas (Raoult et al 2012), Gilthead…”
Section: Discussionmentioning
confidence: 99%
“…For example, MacKenzie et al (2009) found that 'proactive' and 'reactive' carp (Cyprinus carpio) exhibit distinct and sometimes opposite patterns of gene expression under control conditions and in response to an immune challenge. Similarly, Rupia et al (2016) characterized the behavioural and physiological stress responses of olive flounder, Paralichthys olivaceus. They found that flounder with 'bold' behavioural types responded to acute stress by increasing their metabolic rates, whereas 'shy' types decreased their metabolic rates relative to routine.…”
Section: To Estimate Personality-related Measurement Bias In Physiolomentioning
confidence: 99%